PENGARUH TERAPI BIRTHING BALL TERHADAP LAMA KALA 2 PADA IBU BERSALIN DI PMB CITRA DUSUN JAMBESARI DESA MUMBULSARI KABUPATEN JEMBER - Fitriani, Ari; Hamim, Nur; Hanifah, Iis (INVOLUSI: Jurnal Ilmu Kebidanan, 2023)
Labor is the process of moving the fetus out. Prolonged labor can have serious consequences for the mother and fetus, one or both at the same time. Prolonged labor is one of the causes of maternal and fetal death. Long parturition on average causes maternal death in primigravida due to prolongation by 8% in the world and 9% in Indonesia. This study aims to analyze the effect of birthing ball therapy on the length of the second stage of childbirth in PMB Citra Dusun Jambesari, Mumbul Sari Village, Jember Regency. This study used an experimental research design with the static-group comparison design. This research was conducted at PMB Citra, Jambesari Hamlet, Mumbul Sari Village, Jember Regency on all 30 mothers. The sample size in this study was 100% of the population, the sampling technique used was purposive sampling. Data were collected by documentation and analyzed by Mc Nemar statistic with SPSS. The results showed that the duration of the second stage of labor in women who were not given birthing ball therapy experienced a length of labor as many as 10 people (66.7%) and those who were given birthing ball therapy tended to be in accordance with their delivery as many as 11 people (73.3%). Based on the Mac Nemar test, the significance value (Asymp. Sig) was 0.031 < 0.05, meaning that ho was rejected and ha was accepted, so that there was an influence of birthing ball therapy on the duration of the second stage of labor in women giving birth in PMB Citra Hambesari, Mumbulsari Village, Jember Regency. The hypothesis in this study is accepted and statistically proven. It is recommended that mothers can then exclusively breastfeed and be active in posyandu activities.